Alterações em biomarcadores salivares em indivíduos com Anemia ou Traço Falciforme estão associadas às doenças periodontais? - BUONOCORE, Halinna Larissa Cruz Correia de Carvalho (2018)
Introduction: Sickle Cell Anemia (SCA) and Sickle Cell Trait (SC) are genetic conditions linked to the homozygous and heterozygous inheritance, respectively, of an abnormal gene caused by the mutation of the hemoglobin beta globin, causing altered hemoglobin (HbS). Under hypoxic conditions, individuals with higher concentrations of HbS may suffer vaso-occlusive events, causing susceptibility to inflammation and bacterial infections. Periodontal diseases (PDs) are chronic conditions triggered in response to bacterial colonization, and their clinical manifestations are strongly influenced by the host's immune response, in addition to being modulated by other associated factors. Individuals with AF and PD appear to have an altered immunological profile and be more susceptible to bacterial infections, and may be more prone to PD. Therefore, this thesis was divided into two chapters. Chapter I aimed to determine the concentrations of salivary biomarkers (IL-1β, IL-6, MMP-8, TIMP-1, OPG and RANK-L) in individuals with SCA with periodontitis, and investigate the influence of these biomarkers on the relationship between exposure and outcome. Chapter II aimed to investigate the association between bone metabolism biomarkers OPG and RANK-L) and periodontal parameters in individuals with PD. Methods: These are two cross-sectional studies nested within a retrospective cohort. For Article 1, subjects were selected from the Hematology and Hemotherapy Supervision of Maranhão (HEMOMAR) in São Luís, Brazil and were divided into 2 groups: exposed group 1 (with AF) and unexposed group (without AF and TF), with 123 individuals per group (n = 246). For Article 2, only subjects with SSD and the unexposed groups were considered. For article 1, periodontitis was diagnosed by full-mouth assessment of clinical attachment level at 6 sites per the 2018 case definition. Clinical probing depth (PCS), clinical attachment level (CIN), and bleeding at sounding (SS) were evaluated. To the 12 concentrations of salivary biomarkers (IL-1β, IL-6, MMP-8, TIMP-1, RANK-L and OPG) were determined by CBA and ELISA. Biomarkers were grouped by affinity into principal components (PCs) to estimate associations of interest in structural equation modeling (α=0.05). In article 2, the primary outcome was the rate of progression of periodontal disease defined by the ratio between the percentage of bone loss of the worst affected tooth/age and dichotomized into: (1) slow to moderate progression (ratio≤1) and (2) ) rapid progression (ratio>1). The extent of periodontitis was assessed by (1) number of teeth with clinical attachment level (CIN)≥4mm and (2) number of teeth with clinical probing depth (PCS)≥4mm. Crude and adjusted Mean Ratios (MR) and Prevalence Ratios (PR) for sex, socioeconomic class, smoking, alcohol, last visit to the dentist and comorbidities were estimated using Poisson and Logistic regression analyses.Results: In chapter 1, the median salivary concentrations of IL-6, TIMP-1, OPG and RANK-L presented higher values ​​in the AF group when compared to the control group (p<0.001). In individuals diagnosed with periodontitis, the median concentrations of TIMP-1, OPG and RANK-L were higher in the AF group (p<0.001; p=0.006 and p<0.004, respectively). CP1 (IL-1β, IL-6 and MMP-8) and CP2 (TIMP-1, RANK-L and OPG) are correlated with the presence of AF (SC=0.187; p= 0.048 and SC=0.824; p<0.001, respectively). However, concentrations of salivary biomarkers do not act as mediators of the association with periodontitis. In chapter 2, it was found that a higher level of OPG was associated with rapid progression of periodontal disease (RP 2.55, 95%CI 1.11 5.84, p=0.026), the greater number of teeth with CIN≥4mm (RM 1.48, 95%CI 1.18-1.85, p=0.001) and with PCS≥4mm (RM 2 01, 95%CI 1 53 2 63, P<0 001) . The RANK-L/OPG ratio was inversely associated with the number of teeth with PCS≥4mm (RM 0 76, 95%CI 0 59 0 97, p=0 03). Conclusion: Individuals with SCA and TF showed significant changes in the concentrations of salivary biomarkers, which did not explain the occurrence of periodontitis in the SCA group, however, individuals with TF showed changes in salivary biomarkers of tissue destruction (reduction in RANK-L and increase in OPG ), which may reflect changes in bone metabolism that result in a higher rate of progression and greater extent of periodontitis in these individuals.